Tweet or "Re-Tweet"? An experiment of message strategy and interactivity on Twitter. Issue 5 (19th August 2014) - Li, Zongchao; Li, Cong
Abstract : Purpose: Although a large number of prior studies have discussed the impact of using social media to organizations, the existing literature has not yet provided a clear guidance on what specific communication strategy organizations should adopt on social media and what relationship they need to establish with the public. To fill this theoretical gap, the current study examines the effects of message strategy and interactivity from a relationship-building perspective within a social media context. Design/methodology/approach: Through a 2 × 2 between-subjects experiment (N = 84), this study tests the effects of two message strategies, communal-relationship oriented messages and exchange-relationship oriented messages, with either a high or low level of interactivity within a corporate Twitter setting. Findings: The study findings indicate that communication strategies with different relationship orientations differ in quality. Communal-relationship oriented messages tend to generate more favorable relationship outcomes such as trust and control mutuality than exchange-relationship oriented messages. Message interactivity also positively influences attitude toward the company, perceived company credibility, and commitment. Originality/value: The unique contribution of this study is to extend relationship theories to a discussion of what message strategies organizations should use on social media. It suggests that messages oriented toward different relationships can lead to different outcomes. It also demonstrates the effectiveness of message interactivity in building a relationship between an organization and the public.